2013
DOI: 10.2478/s11535-013-0157-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hairy roots in Arnica montana L. by Agrobacterium rhizogenes

Abstract: Abbreviations:MS -Murashige and Skoog medium; B5 -Gamborg's medium; SH -Schenk and Hildebrandt medium; PCR -polymerase chain reaction; MP -micropropagated plants; RP -regenerated plants from callus culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
1
9
0
3
Order By: Relevance
“…The induction of hairy roots culture was described by Petrova et al (2013). The transgenic clone (T4) that showed the best growth characteristics was used to study the effects of sucrose, maltose, and glucose (added to the agar solidified Murashige and Skoog (1962) nutrient medium (MS) at concentrations of 1%, 3%, 5%, 7%, and 9%) on the accumulation of biomass and metabolite production of A. montana hairy roots.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The induction of hairy roots culture was described by Petrova et al (2013). The transgenic clone (T4) that showed the best growth characteristics was used to study the effects of sucrose, maltose, and glucose (added to the agar solidified Murashige and Skoog (1962) nutrient medium (MS) at concentrations of 1%, 3%, 5%, 7%, and 9%) on the accumulation of biomass and metabolite production of A. montana hairy roots.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The infection time influenced the frequency of HR formation. Petrova et al, (2013) reported increased transformation frequency as the infection time increased from 5 to 20 minutes. Short infection time may result in low availability of bacteria for transforming the plant cells while long durations may lead to a decline in the transformation rate by competitive inhibition (Kumar et al, 1991).…”
Section: Effect Of Concentrations Of Bacterial Suspension and Times O...mentioning
confidence: 95%
“…Trong nuôi cấy rễ tơ ở hầu hết các loài thực vật nói chung, sucrose được sử dụng như nguồn carbon thích hợp nhất để thu nhận sinh khối. Thí dụ như dòng rễ tơ T4 từ cây Arnica montana L. cho lượng sinh khối tươi cao nhất trên môi trường có sucrose [18]. Tuy nhiên, trong vài trường hợp, các loại đường khác cũng cho chỉ số tăng trưởng tương đương với sucrose như dòng rễ tơ 14-P từ cây Picrorhiza kurroa [30].…”
Section: Sự Phát Triển Của Rễ Tơ ở Môi Trường Có Nguồn Carbon Khác Nhauunclassified
“…Tuy nhiên, có những dòng rễ tơ có thể phát triển tốt trong một dãy nồng độ sucrose khác nhau. Thí dụ như dòng rễ tơ T4 cây Arnica montana L. tăng trưởng cao nhất ở môi trường có sucrose 3-5% [18] hay như sự phát triển của dòng rễ tơ số 8 từ cây dừa cạn cũng không có sự khác biệt đáng kể giữa trong dãy nồng độ sucrose này [26]. Qua đó có thể thấy nồng độ sucrose có ảnh hưởng khác nhau tùy từng dòng rễ tơ và không phụ thuộc vào loài thực vật.…”
Section: Sự Phát Triển Của Rễ Tơ ở Môi Trường Có Nồng độ Sucrose Khácunclassified